Finding HIV in Hard to Reach Populations: Mobile HIV Testing and Geospatial Mapping in Umlazi Township, Durban, South Africa - Bassett, Ingrid V.; Regan, Susan; Mbonambi, Hlengiwe; Blossom, Jeffrey; Bogan, Stacy; Bearnot, Benjamin; Robine, Marion; Walensky, Rochelle P.; Mhlongo, Bright; Freedberg, Kenneth A.; Thulare, Hilary; Losina, Elena (AIDS and behavior, 2015)
Mobile, community-based HIV testing may help achieve universal HIV testing in South Africa. We compared the yield, geographic distribution, and demographic characteristics of populations tested by mobile- and clinic-based HIV testing programs deployed by iThembalabantu Clinic in Durban, South Africa. From July to November 2011, 4,701 subjects were tested; HIV prevalence was 35 % among IPHC testers and 10 % among mobile testers ( p < 0.001). Mobile testers varied in mean age (22–37 years) and % males (26–67 %). HIV prevalence at mobile sites ranged from 0 to 26 %. Testers traveled further than the clinic closest to their home; mobile testers were more likely to test ≥5 km away from home. Mobile HIV testing can improve testing access and identify testing sites with high HIV prevalence. Individuals often access mobile testing sites farther from home than their nearest clinic. Geospatial techniques can help optimize deployment of mobile units to maximize yield in hard-to-reach populations.